2023
DOI: 10.1021/acs.jpclett.3c00619
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Mediated Photoelectrochemical Hot-Hole Oxidation Coupling Reactions of Adenine on Nanostructured Silver Electrodes

Abstract: Surface-enhanced Raman spectroscopy (SERS) has been widely applied in the identification and characterization of DNA structures with high efficiency. Especially, the SERS signals of the adenine group have exhibited high detection sensitivity in several biomolecular systems. However, there is still no unanimous conclusion regarding the interpretation of some special kinds of SERS signals of adenine and its derivatives on silver colloids and electrodes. This Letter presents a new photochemical azo coupling react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Many kinds of chemical reactions caused by hot-electron transfer have been reported, following pioneering studies, including azo-bond formation, , epoxidation, and H 2 dissociation . In recent years, the generation and utilization of hot holes for chemical reactions have also attracted increasing attention. Recent studies have revealed that hot holes can enhance or induce various chemical reactions such as the oxidative dissolution of Au nanorods, azo coupling reaction of adenine, and oxidative scission of the CC bond, and so on.…”
Section: Diverse Excitation Sourcesmentioning
confidence: 99%
“…Many kinds of chemical reactions caused by hot-electron transfer have been reported, following pioneering studies, including azo-bond formation, , epoxidation, and H 2 dissociation . In recent years, the generation and utilization of hot holes for chemical reactions have also attracted increasing attention. Recent studies have revealed that hot holes can enhance or induce various chemical reactions such as the oxidative dissolution of Au nanorods, azo coupling reaction of adenine, and oxidative scission of the CC bond, and so on.…”
Section: Diverse Excitation Sourcesmentioning
confidence: 99%
“…The energy of harmonic oscillations was calculated for each final geometry [127][128][129], together with the respective theoretical IR intensities and Raman activities. The obtained vibrational energies were not scaled, although in general, it can improve the agreement between calculated and experimental bands [130]. The transformation from Raman activities to excitation-dependent Raman intensities was conducted according to the method described in our earlier studies [131,132].…”
Section: Dft Calculationsmentioning
confidence: 99%
“…have been well-proven in several studies. [5][6][7][8][9][10][11][12][13] This has been extended further to study the reactivity of a range of biomolecules like peptides in a plasmonic hot spot by tipenhanced Raman scattering (TERS). 14 A common explanation of plasmon-induced processes is based on the well-developed models for reactions induced by electronic transitions namely desorption induced by electronic transition (DIET), and desorption induced by multiple electronic transitions (DIMET).…”
Section: Introductionmentioning
confidence: 99%